Halal Determination in View Generation Millennials and Generation Z about Product Halal Awareness Food on Digital Platforms - Aufa Rizka Azzumi; Miswanto Miswanto; Naqiyah Naqiyah (Brilliant International Journal Of Management And Tourism, 2023)
This research explores halal determination among millennials and Generation Z regarding their awareness of halal food on digital platforms. Millennials and Gen Z, influenced by the digital age, exhibit distinct consumption behaviors. With easy internet access and social media engagement, they show heightened awareness of social, environmental, and product quality issues. Understanding their perspectives on halal food awareness on digital platforms is crucial. While previous studies focused on Muslim Gen Y's consumption behavior, little is known about how Muslim Gen Z engages with halal cosmetics in Indonesia. This study investigates Gen Z, characterized by technological proficiency, online connectivity, awareness of current issues, and strong individualism. Understanding their halal awareness helps businesses develop targeted marketing strategies to cater to their needs. This research contributes to consumer behavior knowledge and factors influencing halal food awareness on digital platforms. It enables food producers and digital platforms to devise impactful marketing strategies for these consumer segments